Growth and hematology of pacu subjected to sustained swimming and fed different protein levels - Nunes, Cleujosí da Silva; Moraes, Gilberto; Fabrizzi, Fernando; Hackbarth, Araceli; Arbeláez-Rojas, Gustavo Alberto (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the effect of sustained swimming and dietary protein levels on growth and hematological responses of juvenile pacu (Piaractus mesopotamicus). A completely randomized design was used in a 3x2 factorial arrangement, with three levels of dietary protein (24, 28, and 32% crude protein), two rearing conditions (sustained swimming or motionless water), and 15 replicates. Fish were subjected to sustained swimming at the velocity of two body lengths per second (2 BL s-1), for 45 days. The level of dietary protein and the swimming conditions affected the performance, growth, and hematological profile of pacu. Swimming conditions influenced nutritional factors, increasing daily weight gain, specific growth rate, number of erythrocytes, mean corpuscular volume, and mean corpuscular hemoglobin. Fish under sustained swimming and fed with 24% crude protein showed better growth performance, with higher specific growth rate (4.11±0.88) and higher daily weight gain (2.19±0.47 g per day). Sustained swimming can increase the productive performance of pacu and simultaneously reduce dietary protein levels.